Answer:
![15\pi\ cm^{2}](https://tex.z-dn.net/?f=15%5Cpi%5C%20cm%5E%7B2%7D)
Step-by-step explanation:
we know that
The lateral area of the cone is equal to
![LA=\pi rl](https://tex.z-dn.net/?f=LA%3D%5Cpi%20rl)
where
r is the radius of the base
l is the slant height
we have
![r=3\ cm](https://tex.z-dn.net/?f=r%3D3%5C%20cm)
Applying the Pythagoras Theorem find the slant height
![l^{2}=3^{2} +4^{2}\\ \\l^{2}=25\\ \\l=5\ cm](https://tex.z-dn.net/?f=l%5E%7B2%7D%3D3%5E%7B2%7D%20%2B4%5E%7B2%7D%5C%5C%20%5C%5Cl%5E%7B2%7D%3D25%5C%5C%20%5C%5Cl%3D5%5C%20cm)
substitute in the formula
![LA=\pi (3)(5)=15\pi\ cm^{2}](https://tex.z-dn.net/?f=LA%3D%5Cpi%20%283%29%285%29%3D15%5Cpi%5C%20cm%5E%7B2%7D)
Answer:
40 trees
Step-by-step explanation:
Let the total number of trees be x.
75% of all the sycamore trees in the park are 30 trees.
So,75%of x=30
or,(75/100)*x=30
or,x=(30*100)/75
or,x=40 [ANS]
Answer:
Marion bought 6 frog lures and 8 lizard fishing lures.
Step-by-step explanation:
Let
represent frog lures and
represent lizard lures.
The total packages Marion bought is
![f+l=14...eqn1](https://tex.z-dn.net/?f=f%2Bl%3D14...eqn1)
If she bought frog lures in packages of 4 and lizard lures in packages of 6 for a total of 72 lures, then
![4f+6l=72...eqn2](https://tex.z-dn.net/?f=4f%2B6l%3D72...eqn2)
We make
the subject in equation 1 and put it into equation 2 to get;
![f=14-l...eqn3](https://tex.z-dn.net/?f=f%3D14-l...eqn3)
We put equation 3 into equation 2 to get;
![4(14-l)+6l=72](https://tex.z-dn.net/?f=4%2814-l%29%2B6l%3D72)
![\Righttarrow 2(14-l)+3l=36](https://tex.z-dn.net/?f=%5CRighttarrow%202%2814-l%29%2B3l%3D36)
We expand the bracket to get;
![28-2l+3l=36](https://tex.z-dn.net/?f=28-2l%2B3l%3D36)
![-2l+3l=36-28](https://tex.z-dn.net/?f=-2l%2B3l%3D36-28)
![l=8](https://tex.z-dn.net/?f=l%3D8)
We put
into equation 3 to get;
![f=14-8](https://tex.z-dn.net/?f=f%3D14-8)
![f=6](https://tex.z-dn.net/?f=f%3D6)
Therefore Marion bought 6 frog lures and 8 lizard fishing lures.
Y = 2/7x - 4
y + 4 = 2/7x
4 = 2/7x - y (multiply everything by seven to get rid of the fraction)
28 = 2x - 7y
2x - 7y = 28
Answer:
36÷3÷2÷3=2
Step-by-step explanation: